Diseño de un sistema integrado de gestión alineadoa la estrategia de SPAI-SONS PHAMACEUTICAL INTERNATIONAL COSMETICS basado en modelos ISO 9001:2008 ISO 14001:2004 y OHSAS 18001: 2007 - Ponce de León Toro, Diana Samadhi (Escuela Colombiana de Ingeniería Julio Garavito, 2013)
Este trabajo de grado presenta el diseño del sistema integrado alineado a la estrategia, basado en las normas ISO 9001:2008, ISO 14001:2004 y OHSAS 18001:2007, para SPAI - SONS PHARMACEUTICAL INTERNATIONAL COSMETICS, con el fin de proporcionar un diseño a la organización de como plantear, mantener y lograr controlar la calidad, los aspectos e impactos ambientales y los riegos laborales a los que se encuentra expuesta.

This degree project presents the design of the integrated system aligned with the strategy, based on the ISO 9001: 2008, ISO 14001: 2004 and OHSAS 18001: 2007 standards, for SPAI - SONS PHARMACEUTICAL INTERNATIONAL COSMETICS, in order to provide a design to the organization of how to propose, maintain and achieve quality control, the environmental aspects and impacts and the labor risks to which it is exposed.
Abstract: This degree work shows the design of the integrated strategy aligned, based on the standards ISO 9001:2008, ISO 14001:2004 y OHSAS 18001:2007, for SPAI - SONS COSMETICS INTERNATIONAL PHARMACEUTICAL, in order to provide a design as to the organization of raising, maintaining and achieve control quality, environmental aspects and impacts and occupational hazards to which they are exposed.
Keywords: Calidad; Sistemas integrados de gestión; Seguridad Industrial; Normas; Quality; Industrial Security; Integrated Management Systems; Norms